Microgel PAINT – nanoscopic polarity imaging of adaptive microgels without covalent labelling. Issue 44 (27th September 2019) - Purohit, Ashvini; Centeno, Silvia P.; Wypysek, Sarah K.; Richtering, Walter; Wöll, Dominik
Abstract : The 3D structure and the local environment of stimuli-responsive microgels were investigated with the superresolution fluorescence microscopy method PAINT using Nile Red as solvatochromic dye. Abstract : Polymer nanostructures have enormous potential for various applications in materials and life sciences. In order to exploit and understand their full capabilities, a detailed analysis of their structures and the environmental conditions in them is essential on the nanoscopic scale. With a super-resolution fluorescence microscopy technique known as PAINT (Points Accumulation for Imaging in Nanoscale Topography), we imaged colloidal hydrogel networks, so-called microgels, having a hydrodynamic radius smaller than the diffraction limit, gaining unprecedented insight into their full 3D structure which is not accessible in this much detail with any other experimental method. In addition to imaging of the microgel structure, the use of Nile Red as the solvatochromic fluorophore allowed us to resolve the polarity conditions within the investigated microgels, thus providing nanoscopic information on the x, y, z -position of labels including their polarity without the need of covalent labelling. With this imaging approach, we give a detailed insight into adapting structural and polarity properties of temperature-responsive microgels when changing the temperature beyond the volume phase transition.